PERFORMANCE DIMENSIONS OF SRI LANKAN HOTEL INDUSTRY - Kaluthanthri, Prathap; Osmadi, Atasya (PLANNING MALAYSIA, 2020)
The mixed nature of industrial and service dimension of a hotel including pure service (room service), stock management service (beverage and vendors product), and in-house processing (Food at the restaurant) crafts are a unique business setting for a hotel. In consequence, it creates a challenging task for monitoring the alignment of the strategic plan of the hotel. Hence, the performance of a hotel needs to be measured through a three-dimensional perspective which covers (i) nature of pure service, (ii) product, and (iii) service-product. The measure of the three-dimensional perspective requires empirically validated hotel-specific performance measurement system. The study reviews experts’ views on performance measurement dimensions for the hotel industry in Sri Lanka based on the Analytic Hierarchy Process (AHP). Performance dimensions identified through literature review evaluated by a panel of experts consists of academics, seniors and middle-level management of hotels, government and travel advisory officials, and opinion leaders. The results of AHP on performance dimensions were re-confirmed by applying Content Validity Ratio (CVR) analysis. The AHP order of performance dimensions begins with Competitiveness followed by Finance, Quality, Innovation, Flexibility, Resource utilization, Environment, and Supplier Performance respective. The CVR on AHP order confirmed 6 dimensions on performance measurement for Sri Lankan hotel industry as final selection leaving out environmental and supplier performance from the list of performance dimensions.